Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 749: 140



Work Step by Step

$\frac{1+i}{-3i}\times\frac{-3i}{-3i}$ =$\frac{(1+i)\times -3i}{-3i\times -3i}$ =$\frac{-3i-3i^{2}}{9i^{2}}$ =$\frac{-3i-3(-1)}{9(-1)}$ =$\frac{3-3i}{-9}$ =$\frac{-3(-1+i)}{-9}$ =$\frac{(-1+i)}{3}$ =$-\frac{1}{3}+\frac{1}{3}i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.